2020
DOI: 10.21203/rs.3.rs-35389/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ocular surface manifestation of COVID-19 and tear film analysis

Abstract: Purpose: To evaluate the ocular manifestation in patients hospitalized with coronavirus disease 2019 (COVID-19) and to search for the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in tears.Methods: This study was conducted in 29 hospitalized patients who were admitted to the COVID center at the Policlinic Hospital of the University of Messina, Italy.All patients underwent an ophthalmologic assessment comprising a Standardized Patient Evaluation of Eye Dryness (SPEED) questionnaire, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Conjunctivitis appears to be the most prevalent ophthalmic manifestation of the disease and could potentially be one of the first symptoms of the virus. However, it has been demonstrated that patients infected with SARS-CoV-2 have presented with signs of blepharitis including lid margin hyperemia and/or telangiectasia, crusted eyelashes, and meibomian orifices alterations, potentially owing to the ability SARS-CoV-2 to alter the microenvironment and destabilize the tear film on the ocular surface epithelial cells and glands [ 11 ]. Without further research on the ocular symptoms related to SARS-CoV-2, it is possible that the virus could be overlooked in its early stages and the symptoms may be misidentified as more common causes of conjunctivitis (such as an allergic reaction or bacterial origin) rather than manifestations of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctivitis appears to be the most prevalent ophthalmic manifestation of the disease and could potentially be one of the first symptoms of the virus. However, it has been demonstrated that patients infected with SARS-CoV-2 have presented with signs of blepharitis including lid margin hyperemia and/or telangiectasia, crusted eyelashes, and meibomian orifices alterations, potentially owing to the ability SARS-CoV-2 to alter the microenvironment and destabilize the tear film on the ocular surface epithelial cells and glands [ 11 ]. Without further research on the ocular symptoms related to SARS-CoV-2, it is possible that the virus could be overlooked in its early stages and the symptoms may be misidentified as more common causes of conjunctivitis (such as an allergic reaction or bacterial origin) rather than manifestations of the infection.…”
Section: Discussionmentioning
confidence: 99%